Is your extra X chromosome holding you back? An insight into female education and academic careers in STEMM - Alibhai, Aziza; Saigar, Mariam Moiz; Harding, Emilia; Rutland, Catrin S. (InTechOpen, 2018)
This review discusses whether gender inequality still exists within medical, scientific and engineering academia, with regards to the career development of academic staff. In the 1970s it was suggested that women who are talented and educated with family responsibilities tend to come across problems of self-confidence and identity when attempting to enhance their professional careers, and although many are successful in doing so, others find it more challenging. By the 1990s, it was indicated that the main gender inequality mechanism in academia is the commonly known fact that women’s career development in the academic hierarchy is slower than that of men. In the past 50 years, laws and attitudes of many societies, industries and countries, have changed to promote gender equality. What is the impact of these changes, does inequality still exist and what mechanisms exist to address these issues? This review looks in depth at the links between gender equality and continuing personal and professional development (CPPD), in which individuals at work are educated more about the workplace environment and their job roles and performance. The different types, requirements and success rates of CPPD within the scientific (especially medical) academic community is discussed with an emphasis on gender equality.